Difference in blister fluid penetration after single and multiple doses of ceftriaxone. - LeBel, M (1985)
Plasma and suction skin blister fluid concentrations of ceftriaxone were studied in 12 subjects after intravenous administration of 1 g of ceftriaxone every 12 h (q12h) and 2 g every 24 h (q24h) after single and multiple doses. Ceftriaxone concentrations were determined by high-pressure liquid chromatography. Mean peak plasma concentrations (at the end of the 5-min infusion) were 254.0 and 374.8 micrograms/ml after administration of 1 g q12h after single and multiple doses, respectively. Similarly, with 2 g q24h, maximum levels were 409.6 and 443.5 micrograms/ml. Forty-eight hours after the last dose of ceftriaxone, plasma concentrations were still detectable: 1.2 micrograms/ml after 1 g q12h and 3.0 micrograms/ml after 2 g q24h. Higher ceftriaxone concentrations were observed in blister fluid after multiple doses than after a single dose. Peak concentrations almost doubled in the blister fluid after multiple doses: 36.0 versus 67.0 micrograms/ml and 38.6 versus 68.9 micrograms/ml for 1 g q12h and 2 g q24h, respectively. Elimination half-life of ceftriaxone in the blister (8.3 and 11.5 h) was longer than plasma half-life (6.3 h). With the area under the concentration-time curve ratio, a 113% increase in tissue penetration was observed after multiple doses for the 1 g q12h regimen. The free plasma and blister fluid ceftriaxone concentrations observed at the end of the dosing interval of the 2 g q24h regimen were higher than the MIC for 90% of the susceptible microorganisms and justified the once-a-day use of ceftriaxone.